Mechanical forming of herbal tablets - Yus Aniza, Yusof, Dr.; So'Bah, Ahmad; Aziana Azlin, Abdul Hamid (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s home page at http://www.myiem.org.my/